2017
DOI: 10.1111/pce.13025
|View full text |Cite
|
Sign up to set email alerts
|

The UVB photoreceptor UVR8 mediates accumulation of UV‐absorbing pigments, but not changes in plant morphology, under outdoor conditions

Abstract: UVB radiation is biologically active; in plants, it can induce a range of molecular, biochemical, morphological and developmental responses. Although much progress has been made in elucidating UVB perception and signalling pathways under controlled laboratory conditions, understanding of the adaptive, ecological role of UVB responses is still very limited. In this study, we looked at the functional role of UVR8 under outdoor light conditions, by studying growth, photosynthetic competence and accumulation of UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 56 publications
6
34
0
Order By: Relevance
“…The reduction of maximum plant expansion, as well as an overall increase of leaf phenolic concentrations due to solar UV radiation across both ranges confirms previously observed changes in plant morphology and leaf compounds in response to UV radiation (Suchar and Robberecht , Coffey et al. ). However, it is most notable that these effects were consistent across multiple species, origins and in different regions.…”
Section: Discussionsupporting
confidence: 89%
“…The reduction of maximum plant expansion, as well as an overall increase of leaf phenolic concentrations due to solar UV radiation across both ranges confirms previously observed changes in plant morphology and leaf compounds in response to UV radiation (Suchar and Robberecht , Coffey et al. ). However, it is most notable that these effects were consistent across multiple species, origins and in different regions.…”
Section: Discussionsupporting
confidence: 89%
“…The seasonal I flav trend for higher values in spring and autumn, is likely partly explained by low temperatures experienced by understorey species in these periods. Our I flav trends resembled the seasonal patterns in flavonoids attributed to temperature in an outdoor experiment attenuating UV radiation from different Arabidopsis accessions and genotypes (Coffey et al, 2017;Coffey and Jansen, 2019). Earlier studies have found changes in epidermal UV-transmittance at moderate temperatures ranging from + 9 to 21°C (Bilger et al, 2007), which likely falls within the range of summertime fluctuations in the stands we studied (e.g.…”
Section: Potential Interactions Of Seasonal Changes In Temperature Ansupporting
confidence: 78%
“…czerepanovii growing close to the treeline followed a seasonal time-course from bud burst to senescence (Riipi et al, 2002). Similarly, seasonal changes in the short-term accumulation of flavonoids in Arabidopsis were also found to persist even when UV was attenuated (Coffey et al, 2017). The trends reported in these studies and ours all point to other environmental factors or developmental processes that co-vary seasonally with UV radiation also being implicated in driving trends in flavonoids (Liakoura et al, 2001;Kotilainen et al, 2010;Nenadis et al, 2015;Coffey and Jansen, 2019).…”
Section: Does Uv Radiation Explain the Trends In I Flav ?supporting
confidence: 69%
See 1 more Smart Citation
“…Similarly, a study using higher UV‐A irradiance on barley ( Hordeum vulgare ) found no significant effect on F v /F m (Štroch et al ). However, under unshaded conditions, solar UV‐A radiation has been reported to decrease F v /F m in the Arabidopsis mutant uvr8‐1 (Coffey et al ). Increases in F v /F m for plants that have been cultivated under BL have been reported in many plant species (Goins et al , Matsuda et al , Terfa et al , Hoffmann et al ), yet to our knowledge this is the first study of the effects of BL on ϕ PSII and F v /F m to compare differences among Arabidopsis photoreceptor mutants cry1 cry2, phot1 and uvr8‐2 .…”
Section: Discussionmentioning
confidence: 99%